Gaps in the infant mortality rate according to the mothers’ education level in the provinces along the Argentinean Northwest. Indirect estimation from 2010 data census. - Torres, Victor Eduardo (2020)
Introduction: This paper aims at identifying the gap in the Infant Mortality Rate (IMR) according to the mothers’ education level in six provinces of the Argentinean Northwest (NOA). This is a region that is characterized by having sociodemographic indicators that lag behind the rest of the country. Methodology: In order to estimate the IMR according to the mothers’ education level, the Brass method with Hill’s variant is applied using data from the 2010 census. Moreover, the current infant mortality rate is simulated according to the obtained indicators. Results: The gap between the IMR of women with a lower education level and those with a higher education level is twice or three times higher, whereas the gap considering women of a middle education level and those of the highest level varies between one and two. If these gaps were applied to the official IMR from 2017, more than 10 infant deaths per one thousand of children born alive would correspond to women with middle or low education level. Conclusions: There is inequality in the infant mortality in the NOA region according to the education level of mothers, which is far from other regions in the country or the world. Even if vital statistics attempt at revealing some social determinants of health, especially the education level, this source cannot yet be fully used in the diagnostic and follow-up of said inequalities. Indirect methods, considering their own limitations, can complement these deficiencies.